Theory-driven assessment of intentions and behaviours related to mobility of older inpatients: a survey of patients and healthcare professionals - Herzog Philippe J.; Herzog Rose D. L.; Möri Charlotte; Mooser Blandine; Carole Elodie Aubert (Swiss Medical Weekly, 2024)
BACKGROUND: Low mobility of patients during hospitalisation is associated with adverse outcomes. To successfully change behaviours related to mobility of older hospitalised patients, we need to better understand the mechanisms underlying patient and healthcare professional behaviours. In this study, we thus assessed patient- and healthcare professional-reported intentions and behaviours related to mobility of older patients hospitalised on an acute medical ward, based on a theoretical framework – the Health Action Process Approach (HAPA) model – and on additional barriers and facilitators to mobility.